(untitled) (World Science, 2020)
The aim of the study is to investigate the effectiveness of cilostazol in patients with generalized atherosclerosis (GAS). A comprehensive examination of 65 male patients with proved GAS was performed (lesions of the lower extremities, carotid, mesenteric, coronary, cerebral arteries) and 28 healthy males (comparison group - CG) aged over 60 years. Patients with GAS consisted of 2 groups: GAS1 - patients in addition to basic therapy received cilostazol (C; 100 mg 2 times per day); GAS2 - placebo. Patients with GAS showed a significant deterioration in blood flow (decrease in its volumetric blood flow - FV, increase in peak systolic velocity - PSV) in all studied arteries, episodes of myocardial ischemia according to daily ECG monitoring, decreased cognitive function (CF). In patients with GAS1 on the background of taking C observed improvement (p<0,001) blood flow in the studied arteries (increase in FV and decrease in PSV), decrease in the number and duration of episodes of myocardial ischemia (p<0,01 and p<0,05, respectively), increase distances of painless and maximum walking distance (p<0,01), improvement of CF. The data obtained indicate the effectiveness of C as part of complex therapy in patients with GAS and expediency of further research in this direction to clarify the criteria for its appointment to such patients.